PENGEMBANGAN MODUL AJAR IPAS BERBASIS MASALAH (PBL) PADA JURUSAN NAUTIKA KAPAL PENANGKAP IKAN - Hijrawati Ismail; Kasman, Risqah Amaliah; Muhammad Fadli (Almeera Education, 2024)
This study aims to develop a teaching module used by SMK Cadets majoring in Fishing Vessel Nautical. This module was developed using development research or Research and Development (R&D) which aims to produce or develop a teaching module based on the Problem Based Learning (PBL) learning model in the subject of Science with the topic of Material and Its Changes. The development of this teaching module was carried out using the 4D development model developed by Sivasailam Thiagarajan, Dorothy S. Semmel, and Melvyn I. Semmel with 4 stages, but in this study only 3 stages were used. The results obtained a teaching book on the topic of material and its changes that is valid, practical, and effective.